Language anxiety symptoms, self-efficacy and willingness to communicate among Malaysian university students - Marcus Gee Whai, Kho; Su Hie, Ting; Walftor, Dumin (UPT Balai Bahasa, Universitas Pendidikan Indonesia, 2025)
Oral communication anxiety is a persistent challenge for university students, especially in multilingual settings where English is not the primary language. This study examined the relationships between communication apprehension symptoms, self-efficacy, and language anxiety among Malaysian undergraduates, using Imagined Interaction Theory as a theoretical framework. A total of 358 students from a public university in Sarawak completed a questionnaire, and the data were analysed using SmartPLS structural equation modelling. Descriptive findings revealed elevated levels of language anxiety (M = 3.88, SD = 1.25) and cognitive distress (M = 3.71, SD = 1.28) among respondents. The results indicated that cognitive (β = 0.266, p = 0.001) and physical symptoms (β = –0.137, p = 0.054) significantly predicted higher language anxiety and lower self-efficacy (cognitive: β = 0.186, p = 0.006; physical: β = 0.31, p = 0.000). However, behavioural symptoms showed no significant impact on self-efficacy (β = 0.015, p = 0.786). Self-efficacy did not mediate the effect of anxiety symptoms on language anxiety (p > 0.1 for all paths), but willingness to communicate in English significantly moderated the relationship between self-efficacy and language anxiety (β = –0.084, p = 0.073). These findings suggest that internal cognitive-affective experiences are more influential than outward behaviours in shaping communicative confidence. The study highlights the need for targeted pedagogical strategies, including mental rehearsal and cognitive-behavioural techniques, to support students in managing communication anxiety. Implications are particularly relevant for multilingual educational contexts aiming to enhance students’ English oral communication competence.